The Ever-Increasing Array of Novel Inborn Errors of Immunity: an Interim Update by the IUIS Committee - Tangye, Stuart G.; Al-Herz, Waleed; Bousfiha, Aziz; Cunningham-Rundles, Charlotte; Franco, Jose Luis; Holland, Steven M; Klein, Christoph; Morio, Tomohiro; Oksenhendler, Eric; Picard, Capucine; Puel, Anne; Puck, Jennifer; et al. (Journal of clinical immunology, 2021)
The most recent updated classification of inborn errors of immunity/primary immunodeficiencies, compiled by the International Union of Immunological Societies Expert Committee, was published in January 2020. Within days of completing this report, it was already out of date, evidenced by the frequent publication of genetic variants proposed to cause novel inborn errors of immunity. As the next formal report from the IUIS Expert Committee will not be published until 2022, we felt it important to provide the community with a brief update of recent contributions to the field of inborn errors of immunity. Herein, we highlight studies that have identified 26 additional monogenic gene defects that reach the threshold to represent novel causes of immune defects.